2021
DOI: 10.31695/ijasre.2021.34103
|View full text |Cite
|
Sign up to set email alerts
|

Feng Shui: A Comprehensive Review of its Effectiveness Based on Evaluation Studies

Abstract: After five decades of its presence in the Western European space, the architectural profession, regardless of the popularity of feng shui, has never systematically declared itself about this phenomenon. This is a professional problem. It is equally absurd to dismiss feng shui as a bunch of superstitious nonsense without properly scientifically researching it, as well as its detailed study following all Western science standards, without asking, at least once, whether the fengshui recommendations have the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Mak and Ng (2005) showed that building layouts proposed by architects generally concur with the ideal Fengshui model that was established more than 2,000 years ago. Kryžanowski (2021) suggested that many similarities in building design and floor layouts exist between the Fengshui School, environmental psychology and sustainable design principles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mak and Ng (2005) showed that building layouts proposed by architects generally concur with the ideal Fengshui model that was established more than 2,000 years ago. Kryžanowski (2021) suggested that many similarities in building design and floor layouts exist between the Fengshui School, environmental psychology and sustainable design principles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Feng shui is generally used in designing layouts such as spaces, houses, buildings, parks, or tombs. These must be harmonized with nature to get good luck, health, and harmony for individuals, families, or commercial businesses (Kryžanowski, 2021). The practice of feng shui is done by making detailed observations of the natural environment around it to produce precise calculations (AR, 2022b).…”
Section: The Practices Of Feng Shuimentioning
confidence: 99%